Drivers of Successful Controllership - Weber, Jürgen (Business Expert Press, 2010)
Ebook from IG Library ; This book is about drivers of successful controllership. Successful controllership services provide an imperatively required support to managers, especially in times of change. But what makes controllership services successful? Our book provides the first comprehensive set of answers to this question. We argue it is not the selection of latest tools and techniques but carefully customized services, motivated and skillful employees, and intensive mutual exchanges with managers and open cooperation with other internal service providers. Our book thus addresses managers who want to learn how they best profit from a close collaboration with controllers, and controllers who strive to improve the quality of "their" services to deliver superior performance.